Short-term population dynamics of Helianthemum caput-felis, a perennial Mediterranean coastal plant: a key element for an effective conservation programme. Issue 8 (17th November 2018) - Sulis, Elena; Bacchetta, Gianluigi; Cogoni, Donatella; Fenu, Giuseppe
Abstract : Plant population dynamics is fundamental to identify which parts of the life cycle are important when designing management actions. In this study, the short-term population dynamics of Helianthemum caput-felis (Cistaceae), a perennial plant distributed throughout the western Mediterranean Basin, was investigated by monitoring 98 permanent plots randomly placed along the overall distribution range for three years (2013–2015). Demographic surveys were analysed by Integral Projection Models (IPMs), and the analysis of population growth rates, elasticities, and life table response experiment (LTRE) analyses were performed. Under deterministic conditions, the H. caput-felis population showed a slight increase in the first censuses, but a general population decline followed. This trend was probably due to the shrinkage of plants in the last year, which correlated negatively with reproductive traits. Despite this decline, the population was at equilibrium under the simulated environmental stochasticity. The population dynamics of H. caput-felis followed the general pattern typical for long-lived Mediterranean plants: populations with growth rates closer to the equilibrium in the long term, determinant role of the survival-growth transitions for the population growth rate, slow growth and stasis, longevity of established individuals, shrinkage of medium-large plants, low recruitment rate, high generation times and mean long lifespans. The results of this study, which highlight how conservation measures can be focused on protecting and increasing the number of plants of medium-large size, provide important information for the planning management conservation actions for H. caput-felis and for several Mediterranean plants that show a similar life-history strategy.